فاعلية برنامج ارشادي معرفي سلوكي في تنمية الدافعية للتعلم - خويلد, أسماء; خزور, أسماء; عمامرة, سميرة (جامعة الوادي - University of Eloued, 2023)
هدفت الدراسة الحالية الى الكشف عن مدى فاعلية برنامج إرشادي معرفي سلوكي (من إعداد الباحثات) في تنمية الدافعية للتعلم لدى عينة تجريبية من تلاميذ السنة الرابعة متوسط بمتوسطة الامام حاشي معمر بمدينة الجلفة قدر عددها ب:12 تلميذا وتلميذة، مقارنة بعينة ضابطة من تلاميذ السنة الرابعة متوسط بمتوسطة المجاهد لطرش شعبان بمدينة الجلفة قدر عددها ب:12 تلميذا وتلميذة، واستخدمت الدراسة في عملية جمع المعلومات مقياس الدافعية للتعلم لأحمد دوقة. وتمت المعالجة الإحصائية لنتائج الدراسة باستخدام اختبار "ت" لدلالة الفروق بين المتوسطات، وتوصلت الدراسة الى النتائج التالية: 1-لا توجد فروق ذات دلالة إحصائية بين متوسطات درجات القياس القبلي والبعدي في الدافعية للتعلم للعينة الضابطة. 2- توجد فروق ذات دلالة إحصائية بين متوسطات درجات القياس القبلي والبعدي في الدافعية للتعلم للعينة التجريبية تعزى للبرنامج الإرشادي. 3- توجد فروق ذات دلالة إحصائية بين متوسط درجات العينة الضابطة والتجريبية في القياس البعدي في الدافعية للتعلم تعزى للبرنامج الإرشادي. Abstract: The current study aimed to reveal the effectiveness of a cognitive-behavioral counseling program (prepared by the two researchers) in developing the motivation to learn among an experimental sample of fourth year average students at Imam Hashi Muammar Intermediate School in Djelfa city, estimated at 12 male and female, compared to a control sample of fourth year students. Average in the middle school of Mujahid Tarsh Shaban in the city of Djelfa, its number was estimated at: 12 male and female students, and the study used in the process of collecting information the scale of motivation to learn by Ahmed Duqa. The results of the study were statistically treated using the T-test to indicate the differences between the means, and the study reached the following results: 1- There are no statistically significant differences between the mean scores of the pre and post measurements in the motivation to learn for the control sample. 2- There are statistically significant differences between the mean scores of the pre and post measurements in the motivation to learn for the experimental sample due to the counseling program. 3- There are statistically significant differences between the mean scores of the control and experimental sample in the post measurement in motivation to learn due to the counseling program.
دراسة تجريبية لدى عينة من تلاميذ السنة الرابعة متوسط بمدينة الجلفة
مقال
Keywords: برنامج ارشادي معرفي سلوكي؛ الدافعية للتعلم; Cognitive behavioral counseling program ; Motivation to learn